Família e dependência química: uma relação delicada - Monastero, Leda Fleury (2010)
International and national studies point to substance dependence as one of the most frequent psychiatric disorders of our time that extends far beyond the individual self, but their families are also affected. Today, it is commonly agreed that the concept of a family has been changing, but its function of being a place of care and safety, in several knowledge fields, continues being recognized by scholars and families. Researches on drug addiction include several lines of study addressing from genetic and neurobiological factors to psychological reasons and motivation behind addiction, and they clearly state how harmful they can be to any instance in social, occupational and familiar life. However, studies on addiction recovery and on how arduous it is to addicts to sustain abstinence and prevent relapsing are still rare. This study aimed to develop a social-intervention model towards drug addicts that enables them to re-mean the narratives of their lives lived within family dynamics. Through social and educational monthly meetings, we sought to build a communication channel between the Casa Diar s resident addicts and their families and people interested in the community. This activity was done during this period when addicts struggle to beat their addiction and avoid behavior and attitudes of substance dependents. Topics such as family and group definition, communication, values, beliefs inside a family, differences between behaving and acting among many others were addressed giving room to deconstruct myths and restrictive, negative and repetitive telling about drug addiction and familiar relationships. From these participants telling, this reconstruction could be done through new and re-meant narratives which were born from dialogues and involvement kept during the meetings